Efficient CO2 Electroreduction to Ethanol by Cu3Sn Catalyst. Issue 2 (10th December 2021) - Shang, Longmei; Lv, Ximeng; Zhong, Lixiang; Li, Shuzhou; Zheng, Gengfeng
Abstract: Electrochemical carbon dioxide reduction to ethanol suggests a potential strategy to reduce the CO2 level and generate valuable liquid fuels, while the development of low‐cost catalysts with high activity and selectivity remains a major challenge. In this work, a bimetallic, low‐entropy state Cu3 Sn catalyst featuring efficient electrocatalytic CO2 reduction to ethanol is developed. This low‐entropy state Cu3 Sn catalyst allows a high Faradaic efficiency of 64% for ethanol production, distinctively from the high‐entropy state Cu6 Sn5 catalyst with the main selectivity toward producing formate. At an industry‐level current density of −900 mA cm −2, the Cu3 Sn catalyst exhibited excellent stability for over 48 h in a membrane‐electrode based electrolyzer. Theoretical calculations indicate that the high ethanol selectivity on Cu3 Sn is attributed to its enhanced adsorption of several key intermediates in the ethanol production pathway. Moreover, the life‐cycle assessment reveals that using the Cu3 Sn electrocatalyst, an electrochemical CO2 ‐to‐ethanol electrolysis system powered by wind electricity can lead to a global warming potential of 120 kgCO2‐eq for producing 1 ton of ethanol, corresponding to a 55% reduction of carbon emissions compared to the conventional bio‐ethanol process. Abstract : A sustainable CO2 ‐to‐ethanol electrocatalysis system based on a low‐entropy state Cu3 Sn catalyst has been developed, exhibiting a high partial current density of producing ethanol and excellent selectivity. The life‐cycle assessment revealed that the carbon footprint of this system is 55% less than the bio‐ethanol process, suggesting a promising approach to achieve carbon neutrality.